Regional Lineament Pattern and Morphotectonic Analysis: The Investigation of Geological Structures and Present-Time Relative Tectonic Activity in the Tin Granite Area of Belitung Island, Indonesia - Hutami, Harnanti Yogaputri; Anas, Nur Ayu; Fattah, Erlangga Ibrahim (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2024)
Belitung Island is located on the East Coast of Sumatra and is the southernmost extension of the Southeast Asian granite belt. Despite the flat terrain of the island, numerous granite outcrops provide insight into the past tectonic activities that caused the uplift in the region. This study analyzes the current state of Belitung's tectonic activity by examining its morphotectonic index and lineament pattern. A National Digital Elevation Model (DEMNAS) dataset with a resolution of up to 8.1 m will be used to assess the geological patterns and relative tectonic activity from the surface. The relationship between the regional lineament system and morphotectonic quantification throughout the landforms of Belitung Island will also be considered. The modified Segmented Tracing Algorithm (m-STA) technique extracted the lineament features. The Index of Relative Active Tectonic (IATR) was calculated by averaging several morphotectonic indices, such as asymmetry factors (AF), stream-length index (SL), mountain-front sinuosity (Smf), and valley floor width-height ratio (VF) factors, to quantify the relative tectonic activity of the area. The combination of the two methods shows that Belitung is currently experiencing relatively weak tectonic activity compared to the past. This is supported by the surface appearance, which is mainly composed of lowlands. Several granite outcrops and highlands are aligned along the NW-SE and NE-SW directions, corresponding to the main geological structures in the area.